Genetic analysis of CFH and MCP in Egyptian patients with immune-complex proliferative glomerulonephritis - Gouda, Heba R.; Talaat, Iman M.; Bouzid, Amal; El-Assi, Hoda; Nabil, Amira; Venkatachalam, Thenmozhi; Manasa Bhamidimarri, Poorna; Wohlers, Inken; Mahdami, Amena; EL-Gendi, Saba; ElKoraie, Ahmed; Busch, Hauke; et al. (Frontiers in Immunology, 2022)
Glomerulonephritis (GN) is a complex disease with intricate underlying pathogenic mechanisms. The possible role of underlying complement dysregulation is not fully elucidated in some GN subsets, especially in the setting of autoimmunity or infection. In the current study, diagnosed cases of lupus nephritis (LN) and post-infectious GN (PIGN) were recruited for molecular genetic analysis and targeted next-generation DNA sequencing was performed for two main complement regulating genes: in the fluid phase; CFH, and on tissue surfaces; MCP. Three heterozygous pathogenic variants in CFH (Q172*, W701*, and W1096*) and one likely pathogenic heterozygous variant in MCP (C223R) have been identified in four of the studied LN cases. Additionally, among the several detected variants of uncertain significance, one novel variant (CFH:F614S) was identified in 74% of the studied LN cases and in 65% of the studied PIGN cases. This variant was detected for the first time in the Egyptian population. These findings suggest that subtle mutations may be present in complement regulating genes in patients with immune-complex mediated category of GN that may add to the disease pathogenesis. These findings also call for further studies to delineate the impact of these gene variants on the protein function, the disease course, and outcome.